Microbes Attaching to Endoparasitic Phytonematodes in Soil Trigger Plant Defense Upon Root Penetration by the Nematode - Topalović, Olivera; Bredenbruch, Sandra; Schleker, A. Sylvia S.; Heuer, Holger (Frontiers in Plant Science, 2020)
Root-knot nematodes (Meloidogyne spp.) are among the most aggressive phytonematodes. While moving through soil to reach the roots of their host, specific microbes attach to the cuticle of the infective second-stage juveniles (J2). Reportedly, the attached microorganisms affect nematodes and reduce their performance on the host plants. We have previously shown that some non-parasitic bacterial strains isolated from the cuticle of Meloidogyne hapla in different soils affected J2 mortality, motility, hatching and root invasion. Here we tested whether cuticle-attached microbes trigger plant defences upon penetration of J2. In in vitro assays, M. hapla J2-attached microbes from a suppressive soil induced pathogen-associated, molecular pattern-triggered immunity (PTI) in tomato roots. All tested PTI-responsive defence genes were upregulated after root invasion of J2 with attached microbes, compared to surface-sterilized J2, particularly the jasmonic acid-mediated PTI marker genes TFT1 and GRAS4.1. The strain Microbacterium sp. K6, that was isolated from the cuticle, significantly reduced root invasion when attached to the J2. Attached K6 cells supported plant defence and counteracted suppression of plant basal defence in roots by invaded J2. The plant response to the J2-attached K6 cells was stronger in leaves than in roots, and it increased from 1 to 3 days post inoculation (dpi). At 1 dpi, the plant responded to J2-attached K6 cells by ameliorating the J2-triggered down-regulation of defense genes mostly in roots, while at 3 dpi this response was systemic and more pronounced in leaves. In an ROS assay, the compounds released from J2 with attached K6 cells triggered a stronger ROS burst in tomato roots than the compounds from nematodes without K6, or the metabolites released from strain K6 alone. Leaves showed a 100 times more sensitive response than roots, and the metabolites of K6 with or without J2 induced strong ROS bursts. In conclusion, our results suggest the importance of microorganisms attach to M. hapla in suppressive soil, inducing early basal defences in plants and suppressing nematode performance in roots.